Pengaruh Penggunaan Target Net dan Target Bawah Terhadap Servis Panjang Forehand Bulutangkis Pada Anak Usia 11-13 Tahun di PB CPLUSco Semarang - Avita Dia Ayuningrum; Galih Dwi Pradipta Pradipta; Bertika Kusuma Prastiwi Prastiwi (Journal of Physical Activity and Sports (JPAS), 2021)
This research is a quantitative research, data collection using a quasi-experimental method with a research design of two groups pre-test-post-test design. The population in this study were 28 athletes of PB CPLUSco Semarang. The sample selection used in this research was purposive sampling and the samples were 12 athletes. The instrument in this study used a long service accuracy test proposed by Jemes Poole. The normality test results on the net target of 0.741 and the lower target of 0.818, in both groups had a value of more than ? = 0.05, normally distributed. Homogeneity test on the pretest data of 0.488 and posttest of 0.87 had a value of more than 0.05, the two groups of exercises had homogeneous data variants. The results of the paired sample t-test for the net target training group obtained t count -14.6 and the lower target tcount -10,271 with both groups known to have a significance value of 0.000 <0.05, then H_0 is rejected and there is an effect of net target and lower target training treatment on forehand long service accuracy. In the independent sample t test, lower target training is more effective in efforts to improve badminton forehand long service delivery. This is evidenced by obtaining data on the increase in the lower target which has an increase percentage of 32% and a net target of 30%. Based on the results of the study, it can be concluded that the lower target training is more effective than the net target in an effort to increase the accuracy of the badminton forehand long service because the shuttlecock bounces the parabola backward. Suggestions given by researchers 1) The trainer can provide an effective and efficient training program. 2) For athletes to be more earnest in performing forehand long serve. Abstrak Penelitian ini merupakan penelitian kuantitatif, pengambilan data menggunakan metode quasi ekperimental dengan desain penelitian two group pre-test-post-test design. Populasi dalam penelitian ini adalah atlet PB CPLUSco Semarang yang berjumlah 28 atlet. Pemilihan sampel penelitian ini menggunakan purposive sampling dan sempel penelitian berjumlah 12 atlet. Instrumen dalam penelitian ini menggunakan tes ketepatan servis panjang yang dikemukakan oleh Jemes Poole. Hasil uji normalitas pada target net 0.741 dan target bawah 0.818, pada kedua kelompok memiliki nilai lebih dari , berdistribusi normal. Uji Homogenitas pada data pretest 0,488 dan posttest 0,87 memiliki nilai lebih dari 0,05, kedua kelompok latihan memiliki varian data yang homogen. Hasil uji paired sample t-test kelompok latihan target net diperoleh thitung -14,6 dan target bawah thitung -10.271 dengan kedua kelompok diketahui nilai signifikansi sebesar , maka  ditolak dan ada pengaruh treatment latihan target net dan target bawah terhadap ketepatan servis panjang forehand. Pada uji independent sample t test, latihan target bawah lebih efektif dalam upaya peningkatan ketepetan servis panjang forehand bulutangkis. Hal itu dibuktikan dengan diperolehnya data peningkatan target bawah memiliki presentase peningkatan sebesar 32% dan target net sebesar 30%.Berdasarkan hasil penelitian dapat disimpulkan bahwa latihan target bawah lebih efektif  dibandingkan target net dalam upaya peningkatan ketepatan servis panjang forehand bulutangkis karena shuttlecock melambung parabola kebelakang.. Saran yang diberikan peneliti 1) Pelatih dapat memberikan program latihan yang efektif dan efisien. 2) Untuk atlet agar lebih bersungguh-sungguh dalam melakukan servis panjang forehand. Kata Kunci : target net, target bawah, servis panjang, bulutangkis.